Preparation of refractive-index-controlled silicone microspheres and their application in polycarbonate light diffusing materials. Issue 16 (2nd November 2019) - Ouyang, Xing; Lei, Shuai; Liu, Xiaofei; Chen, Dazhu; Tang, Jiaoning
ABSTRACT: Light-diffusing materials (LDMs) are essential for diffusing indoor light-emitting diode (LED) illumination to soft light. The size and refractive index of the light-diffusing agent are the two main parameters that influence the light-diffusing properties of LDMs. Modulation of silicone microspheres' refractive index and their influence on the light-diffusing properties of LDMs were systematically explored. An environmentally friendly, dispersant-free polymerization method carried out in an aqueous solution was developed for the preparation of silicone microspheres with different refractive indices. The prepared microspheres and LDMs were characterized by scanning electron microcopy (SEM), Fourier transform infrared (FTIR) spectroscopy and thermogravimetric analysis (TGA). Results showed that the refractive index of the prepared microspheres can be regulated by adjusting the copolymerization composition. Prepared silicone microspheres could be uniformly dispersed in a polycarbonate (PC) matrix, and the refractive index had a marked influence on the light-diffusing properties of the resulting LDMs. The silicone microspheres and LDMs both exhibited excellent thermal stabilities. Graphical abstract: